Design of a temperature-feedback controlled automated magnetic hyperthermia therapy device - Sharma, Anirudh; Jangam, Avesh Avinash; Yung Shen, Julian Low; Ahmad, Aiman; Arepally, Nageshwar; Carlton, Hayden; Ivkov, Robert; Attaluri, Anilchandra (Frontiers in Thermal Engineering, 2023)
Magnetic hyperthermia therapy (MHT) is a minimally invasive adjuvant therapy capable of damaging tumors using magnetic nanoparticles exposed radiofrequency alternateing magnetic fields. One of the challenges of MHT is thermal dose control and excessive heating in superficial tissues from off-target eddy current heating. We report the development of a control system to maintain target temperature during MHT with an automatic safety shutoff feature in adherence to FDA Design Control Guidance. A proportional-integral-derivative (PID) control algorithm was designed and implemented in NI LabVIEW®. A standard reference material copper wire was used as the heat source to verify the controller performance in gel phantom experiments. Coupled electromagnetic thermal finite element analysis simulations were used to identify the initial controller gains. Results showed that the PID controller successfully achieved the target temperature control despite significant perturbations. Feasibility of PID control algorithm to improve efficacy and safety of MHT was demonstrated.